Coarctation of aorta in a young female with extensive collaterals presenting with secondary hypertension - KC, Bishal; Dhungel, Sachin; Gautam, Samir; Khan, Mazhar; Ullah, Aziz (Nepalese Heart Journal, 2022)
Coarctation of aorta is a common condition usually diagnosed during childhood. During adulthood they are usually diagnosed during evaluation of secondary hypertension or resistant hypertension.  We report a case of young female who was asymptomatic and found to have high blood pressure during routine clinical evaluation.  During physical examination she had absent femoral pulses which lead to suspicion of presence of coarctation. She underwent surgical procedure with interposition graft. After follow up of one year she is doing well and her blood pressure under control with a single medication.